Steering the Selectivity in the Ullmann Reaction of Br4TPP on Ag(111) via CO Molecules - Sun, Wei; Wang, Hongbing; Liang, Zhaofeng; Huang, Chaoqin; Ma, Jingyuan; Xie, Lei; Song, Fei (Journal of physical chemistry. C, 2025)
Feasible regulation of molecular architectures requires significant determinations in nanoelectronics, and the introduction of gas molecules is proposed as an effective alternative. While the structural transformation of organometallic species is generally investigated in surface Ullmann coupling, the interaction between intermediate states and gas molecules is still in its infancy. Herein, we demonstrate the manipulation of CO molecules on the selectivity of surface Ullman reactions derived from the dehalogenative reaction of 7,8,17,18-tetrabromo-5,10,15,20-tetraphenylporphyrin (Br4TPP) molecules assembled on the Ag(111) surface, and the significant structure transformation of the surface-adatom-based organometallic species. With a combination of scanning tunneling microscopy, near ambient pressure X-ray photoelectron spectroscopy, density functional theory modeling, and ab initio molecular dynamics simulations, we propose that the CO molecule would first break the C–Ag–C bond by adsorption on the Ag node with a tilted configuration, and the structural transition is correspondingly resulted from a porous C–Ag–C network to a neat Kagome lattice composed of 3 Ag moieties. Importantly, the delicate interaction with CO is witnessed to efficiently tune the reaction pathway by locally confining the TPP species on the surface, preventing the formation of covalent polymers as observed in the conventional Ullmann coupling. Consequently, our study demonstrates the potential of CO molecules to modulate the on-surface synthesis, providing a new avenue toward the rational design of low-dimensional materials.